An investigation into yeast-baculovirus synergism for the improved control of Thaumatotibia leucotreta, an economically important pest of citrus - Van der Merwe, Marcél (Rhodes University, Faculty of Science, Department of Biochemistry and Microbiology)
A mutualistic association between Cydia pomonella and yeasts belonging to the genus Metschnikowia has previously been demonstrated. Larval feeding galleries inoculated with M. andauensis, reduced larval mortality and enhanced larval development. Additionally, adult C. pomonella female oviposition preference was also shown to be influenced by the volatiles produced by M. andauensis. This mutualistic relationship was manipulated for biological control purposes, by combining M. pulcherrima with the baculovirus Cydia pomonella granulovirus. The combination of M. pulcherrima with brown cane sugar and CpGV in laboratory assays and field trials resulted in a significant increase in larval mortality. A similar observation was made when M. pulcherrima was substituted for Saccharomyces cerevisiae. This indicates that yeasts harbour the potential for use in biological control, especially when combined with other well-established biocontrol methods. Thaumatotibia leucotreta is a phytophagous insect endemic to southern Africa. It is highly significant to the South African citrus industry due to its classification as a phytosanitary pest by most international markets. An integrated pest management programme has been implemented to control T. leucotreta. The baculovirus Cryptophlebia leucotreta granulovirus forms one component of this programme and is highly effective. In this study, we proposed to determine which yeast species occur naturally in the gut of T. leucotreta larvae and to examine whether any of the isolated yeast species, when combined with the CrleGV-SA, enhance its effectiveness. Firstly, Navel oranges infested with T. leucotreta larvae were collected from geographically distinct citrus-producing regions across South Africa. This led to the isolation and identification of six yeast species from the gut of T. leucotreta larvae via PCR amplification and sequencing of the internal transcribed spacer region and D1/D2 domain of the large subunit. Six yeast species were identified, viz. Meyerozyma guilliermondii, Hanseniaspora uvarum, Clavispora lusitaniae, Kluyveromyces marxianus, Pichia kudriavzevii and Pichia kluyveri. Additionally, Saccharomyces cerevisiae was included as a control in all trials due to its commercial availability and use in the artificial diet used to rear T. leucotreta. Secondly, larval development and attraction assays were conducted with the isolated yeast species. Thaumatotibia leucotreta larvae that fed on Navel oranges inoculated with M. guilliermondii, P. kluyveri, H. uvarum, and S. cerevisiae had accelerated developmental periods and reduced mortality rates. Additionally, it was demonstrated that T. leucotreta neonates were attracted to YPD broth cultures inoculated with P. kluyveri, H. uvarum, P. kudriavzevii and K. marxianus for feeding. Thirdly, oviposition preference assays were conducted with adult T. leucotreta females to determine whether the isolated yeast species influence their egg-laying in two-choice and multiple-choice tests. Navel oranges were inoculated with a specific yeast isolate, and mated adult females were left to oviposit. Meyerozyma guilliermondii, P. kudriavzevii and H. uvarum were shown to influence adult T. leucotreta female oviposition preference in two-choice tests. However, multiple-choice tests using the aforementioned yeast species did not mimic these results. Lastly, a series of detached fruit bioassays were performed to determine the optimal yeast:virus ratio, test all isolated yeast species in combination with CrleGV-SA and to further enhance yeast/virus formulation through the addition of an adjuvant and surfactant. CrleGV-SA was applied at a lethal concentration that would kill 50 % of T. leucotreta larvae. The optimal yeast concentration to use alongside CrleGV-SA was determined. Pichia kluyveri, P. kudriavzevii, K. marxianus and S. cerevisiae in combination with CrleGV-SA increased larval mortality compared to CrleGV-SA alone. The inclusion of molasses and BREAK-THRUÂ® S 240 to P. kudriavzevii and S. cerevisiae plus CrleGV-SA formulations greatly enhanced their efficacy. Additionally, semi-field trials were initiated using P. kudriavzevii and S. cerevisiae, with promising preliminary results being obtained, although more replicates need to be performed. The experiments performed in this study provide a platform for further research into the application of a yeast/virus combination as a novel control and monitoring option for T. leucotreta in the field.
Keywords: Baculoviruses; Cryptophlebia leucotreta; Yeast; Natural pesticides; Citrus -- Diseases and pests; Biological pest control agents; Pests -- Integrated control; Thaumatotibia leucotreta